2014
DOI: 10.1007/s13592-014-0313-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of honeybee, Apis mellifera, larva chymotrypsin-like protease

Abstract: International audiencePreviously, we found three enzyme fractions containing activities for the hydrolysis of royal jelly proteins from honeybee queen larvae. In this study, we identified a honeybee chymotrypsin-like protease (HCLPase) by LC-MS/MS and expressed it as a recombinant protein in Escherichia coli. The protease had an estimated molecular weight of around 26 kDa and showed high specificity for succinyl-Ala-Ala-Pro-Phe p-nitroanilide as a proteolytic substrate. Furthermore, the protease had an optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Dahlmann and coauthors observed chymotryptic proteases in both larval and adult bees, while tryptic proteases only in adult bees, which is not in accordance with our results. Recently, a chymotrypsin‐like protease from honeybee larvae was found and characterized , suggesting a role in food digestion. The absence of these proteinases in the prepupae from infected bees could be caused by the degradation of the peritrophic matrix and the attack of the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dahlmann and coauthors observed chymotryptic proteases in both larval and adult bees, while tryptic proteases only in adult bees, which is not in accordance with our results. Recently, a chymotrypsin‐like protease from honeybee larvae was found and characterized , suggesting a role in food digestion. The absence of these proteinases in the prepupae from infected bees could be caused by the degradation of the peritrophic matrix and the attack of the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among proteins, the proteases, mainly the proteinases (endopeptidases) are involved in several physiological and regulatory processes . Since proteases expression could be a mechanism by which honeybee react to the infection, the aim of this work was to compare production of proteases in worker prepupae originating from healthy colonies and from colonies affected by AFB.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of HCLPase expressed in SF9 were the same as that expressed in E. coli, except for its specific activity. Although we previously expressed HCLPase in E. coli as a GST-tagged protein, 9) the characteristics of HCLPase expression were different from the present HCLPase expressed as SUMO-tagged protein in several respects. In the GST-tagged HCLPase, the enzyme had lower specific activity, showed optimal activity at 40°C and pH 9, and was not inhibited by TPCK.…”
mentioning
confidence: 60%
“…8) The recombinant HCLPase expressed in Escherichia coli produced a 26-kDa protein that had chymotryptic activity. 9) In this study, a recombinant HCLPase expressed in SF9 insect cells as eukaryotic cells was produced, and its characteristics were compared to the recombinant protein expressed in E. coli.…”
mentioning
confidence: 99%
“…TPCK and chymostatin, being potent inhibitors of chymotrypsin, inhibited the chymotrypsin‐like enzyme activity in the present study. In contrast, TPCK and TLCK did not affect the chymotrypsin‐like enzyme activity in T. molitor larvae and Apis mellifera (Elpidina et al., ; Matsuoka et al., ). Serine protease inhibitors, PMSF, aprotonin, leupeptin, pefabloc, and antipain completely inhibited the activities of both the enzymes.…”
Section: Discussionmentioning
confidence: 99%